A study on job satisfaction in the consultancy industry - SIVANANDAM, DR. PRASANNA; MS. GAYATHRI.G, (The journal of contemporary issues in business and government, 2020)
In this paper, I study about employee job satisfaction where employees need organisational and personal satisfaction. Employee job satisfaction is the key to success for any company. Job satisfaction is the key indicator of their attitude towards their work, superior and environment. This study is to find about the level of satisfaction in the consultancy industry through implementation of a job satisfaction survey. Due to the stressful work environment prevailing in the companies, the physical health and mental well-being of the employees are at stake. Satisfaction is important because it improves the firm’s ability to predict needs and employee dissatisfaction. The sample size is 30. Using a unique combination of firm-level data and information from job satisfaction surveys, the empirical analysis reveals that the employee needs job security at the most.